2005
DOI: 10.1523/jneurosci.3726-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

The HVC Microcircuit: The Synaptic Basis for Interactions between Song Motor and Vocal Plasticity Pathways

Abstract: Synaptic interactions between telencephalic neurons innervating descending motor or basal ganglia pathways are essential in the learning, planning, and execution of complex movements. Synaptic interactions within the songbird telencephalic nucleus HVC are implicated in motor and auditory activity associated with learned vocalizations. HVC contains projection neurons (PNs) (HVC RA ) that innervate song premotor areas, other PNs (HVC X ) that innervate a basal ganglia pathway necessary for vocal plasticity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
206
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(226 citation statements)
references
References 65 publications
(107 reference statements)
18
206
2
Order By: Relevance
“…The slow and fast time constants τ 1 and τ 2 had respectively the values 1.1 ms and 0.2 ms to match roughly the 4.0 ms onset-to-peak time constants observed in paired intracellular recordings of HVC RA neurons [20]. The value I 0 = 0.3 nA was chosen to give a 1.0 mV peak excitatory post-synaptic potential (EPSP) which is consistent with experiment [20].…”
Section: A a Homogeneous 1d Chain Of Excitatory Neuronsmentioning
confidence: 69%
See 1 more Smart Citation
“…The slow and fast time constants τ 1 and τ 2 had respectively the values 1.1 ms and 0.2 ms to match roughly the 4.0 ms onset-to-peak time constants observed in paired intracellular recordings of HVC RA neurons [20]. The value I 0 = 0.3 nA was chosen to give a 1.0 mV peak excitatory post-synaptic potential (EPSP) which is consistent with experiment [20].…”
Section: A a Homogeneous 1d Chain Of Excitatory Neuronsmentioning
confidence: 69%
“…Of special importance for this paper is the experimental observation that HVC RA neurons synapse with other HVC RA neurons [20]. Thus it is possible for a feedforward network of excitatory neurons to exist in HVC, although we emphasize that there is no evidence presently for such a network.…”
Section: A a Homogeneous 1d Chain Of Excitatory Neuronsmentioning
confidence: 97%
“…Then, a subject-adaptive WOI threshold was established using the 75% rise time from N200 amplitude to P300 amplitude (i.e. the time to reach 75% of the P300 peak amplitude (Mooney and Prather, 2005)). …”
Section: Identification Of Erp Componentsmentioning
confidence: 99%
“…Intracellular electrophysiological studies have so far demonstrated that the burst spikes in HVC X neurons arise through different subthreshold processes from those in HVC RA neurons (Lewicki, 1996;Mooney, 2000;Mooney and Prather, 2005;Long et al, 2010): the temporal precision of HVC RA bursts is mainly determined by selective excitatory synaptic inputs, whereas inhibitory synaptic inputs play primary roles in the establishment of HVC X bursts. Because inhibitory synaptic inputs to HVC X neurons presumably originate from interneurons within HVC, syntactic attributes in HVC X activity may be formed through the development of inhibitory interneurons after the establishment of the excitatory network.…”
Section: Development Of Syntactic Selectivitymentioning
confidence: 99%